Exploring the meaning of community for older Australians. (29th December 2015) - Hoyle, Melanie; Ryan, Carly; Gustafsson, Louise
Abstract : Background/aim: As the population ages, older adults are being encouraged through policy to remain living in their home and community. Occupational therapists are in a position to support individuals to engage in meaningful occupations, acknowledging the influence of personal and environmental factors on community participation. The purpose of this study was to understand the meaning and experience of community for older Australian adults. Methods: A cross‐sectional phenomenological research study design was utilised. Convenience and snowball sampling were used to recruit 32 participants with ages ranging from 65 to 94 years living in the south east region of Queensland, Australia. Semi‐structured interviews were conducted and thematic analysis was used to explore the participants' responses. Results: Four final themes were revealed: organised things in the community, community is people, community is what you make of it and the meaning of community is life. Conclusion: The results support that community extends beyond physicality, with personal motivation, the social environment and community involvement identified as important constructs within each of the themes. The findings provide a foundation for future research and occupational therapy practices to support older adults to age in place.